If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + 1 = 28 Reorder the terms: 1 + 3b = 28 Solving 1 + 3b = 28 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3b = 28 + -1 Combine like terms: 1 + -1 = 0 0 + 3b = 28 + -1 3b = 28 + -1 Combine like terms: 28 + -1 = 27 3b = 27 Divide each side by '3'. b = 9 Simplifying b = 9
| 0.06(a+200)+0.01a=172 | | x/9-9=8 | | 3(x+5)+4(x-3)+-6x=4 | | (8x^2-7x+2)+(3x^2-9x-6)= | | 2(x-4)+x-y=2y-9 | | -8(x-7)-9=47 | | 2(s+6)+2(s-1)+-4=74 | | (5z-9)(8+z)=0 | | x/3=4x/21-7 | | 60x-50=15x-5 | | x/3=4x/21 | | 13-4y+1y= | | 3(m+3)+5(m+1)+-6m=50 | | m=40 | | 6x+3(-3x-7)=0 | | 5x+15=x-20 | | 9xsquared-21=0 | | X-6-x-4=10-c | | -104=5x-3(5x+8) | | .5f=c+6u | | -3+5(b+4)+4(b+3)=2 | | x^(-3/5)=27 | | -7x-6(2x+5)=84 | | 3(n+3)+-2n+2(n+4)=65 | | 8-5x=2c-9x | | 16l=4c^2+9 | | -x/6=5-8 | | 12(t+2)+-7t+-8=6 | | 5x=48+x | | 6sec(x)+8=-4 | | 38.00=0.12m+8 | | -3(-6v+6)-v=2(v-8)-7 |